INTRPERITONEAL INJECTION OF GABA B RECEPTOR ANTAGONIST (CGP 35348) FOLLOWING NEONATAL BRAIN DAMAGE AFFECTS THE BLOOD CHEMISTRY IN ALBINO MICE - N. Khadim; S. Iqbal; Q. A. Gillani; F. Iqbal (Journal of Animal and Plant Sciences, 2014)
Aim of this study was to demonstrate the effect of GABA B receptor antagonists (CGP 35348) on hematological and serum biochemical profile of albino mouse injected for 12 days following neonatal hypoxic ischemic insult. Blood samples from 35 albino mice [CGP35348 treated (N = 19) and saline treated (N= 16)] were collected from direct cardiac puncture and various hematological [blood glucose, packed cell volume (PCV), total WBC count, total RBC count] and selected serum biochemical parameters (cholesterol, AST, ALT, HDL, LDL total protein, triglycerides) were determined. Glucose (P < 0.001), TRBC (P < 0.001), MCV (P < 0.001), TWBC (P = 0.02) and PCV (P = 0.005) concentrations were significantly lower in CGP35348 treated as compared to saline treated albino mice. Gender based data analysis revealed that CGP 35348 had more drastic effects in blood chemistry of female than male albino mice as glucose (P = 0.002) and TRBC (P = 0.007) were the only significantly different parameters when compared between GABAB receptor antagonist and saline treated male albino mice while glucose (P = 0.01), TRBC (P = 0.01), TWBC (P = 0.01), PCV (P = 0.01) and MCV (P = 0.047) concentrations were significantly lower in CGP 35348 treated female albino mice than their respective control group indicating gender specific effect of hypoxic ischemic brain damage and CGP 35348 in albino mice.
Keywords: GABAB receptor antagonist; Hypoxia ischemia; Albino mouse; Hematology; Serum biochemistry